Comparison of taxation of personal income in Canada and the Czech Republic - Písecká, Renáta (2024)
This diploma thesis deals with personal income taxation in Canada, its tax system and legislative procedures. However, the main aim of this thesis is to compare personal income taxation in Canada and the Czech Republic, to which is mainly devoted the last part of the first chapter and then second half of the thesis. The final part consists of using a model example for the practical application of various tax rules in different countries. It also evaluates whether it would be beneficial and feasible to apply certain procedures and rules used for calculating personal income tax in Canada to the context of the Czech Republic.